High burden of cardiometabolic risk factors in spouses of Indian women with hyperglycaemia in pregnancy. Issue 6 (20th March 2020) - Gupta, Y.; Goyal, A.; Kalaivani, M.; Singhal, S.; Bhatla, N.; Gupta, N.; Tandon, N.
Abstract: Aim: To evaluate the burden and association of cardiometabolic risk factors in the spouses of women with and without hyperglycaemia in pregnancy. Methods: Women with ( n  = 204) and without ( n  = 197) hyperglycaemia in pregnancy, along with their spouses, participated in this cross‐sectional study. The hyperglycaemia in pregnancy group included women with gestational diabetes and diabetes in pregnancy. A detailed questionnaire was completed for all participants (men and women), documenting relevant personal and medical history, along with biochemical investigations (men). Results: A total of 401 couples were evaluated at the time point during the pregnancy of 24.7 ± 5.2 gestational weeks (mean ± sd) . Dysglycaemia (prediabetes or diabetes), overweight/obesity (BMI ≥25 kg/m 2 ) and metabolic syndrome were detected in 120 (58.9%), 123 (60.3%) and 98 spouses (48.3%) of women with hyperglycaemia in pregnancy, respectively. In the fully adjusted model, an increased risk of dysglycaemia [odds ratio 1.43 (95% CI 0.95–2.17); P  = 0.088], overweight/obesity [odds ratio 1.49 (95% CI 0.98–2.27); P  = 0.064] and metabolic syndrome [odds ratio 2.00 (95% CI 1.30–3.07); P  = 0.001] was seen in the spouses of women with hyperglycaemia in pregnancy. The prevalence of these metabolic conditions was higher in spouses of women with diabetes in pregnancy compared to spouses of women with gestational diabetes mellitus. Conclusions: A high burden of cardiometabolic risk factors was observed in the spouses of women with hyperglycaemia in pregnancy. The opportunity provided by pregnancy could be used by the healthcare system not only to improve the health of the woman and her offspring, but also her spouse. What's new?: This study evaluates for the first time the risk of adverse cardiometabolic traits in spouses of women with hyperglycaemia in pregnancy. A high burden of cardiometabolic risk factors was observed among the spouses of women with hyperglycaemia in pregnancy. The risk in spouses increased in relation to the degree of hyperglycaemia observed in the pregnant women. Efforts should be made to identify such high‐risk partners by screening during routine antenatal care. Family intervention trials should involve the spouse as a target of intervention and not merely as a supportive partner.